2018
DOI: 10.1002/brb3.1017
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine gene methylation patterns are associated with obesity markers and carbohydrate intake

Abstract: IntroductionDopamine (DA) is a neurotransmitter that regulates the rewarding and motivational processes underlying food intake and eating behaviors. This study hypothesized associations of DNA methylation signatures at genes modulating DA signaling with obesity features, metabolic profiles, and dietary intake.MethodsAn adult population within the Methyl Epigenome Network Association project was included (n = 473). DNA methylation levels in white blood cells were measured by microarray (450K). Differentially me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 74 publications
1
16
0
Order By: Relevance
“…Previously, it was reported that Slc6a3 was hypermethylated in the promoter region in response to high-fat-sucrose diet and downregulated in the nervous system of prenatally stressed female rats and murine models of diet-induced obesity [46,47]. In addition, methylation aberrations at SLC6A3 gene were related to triglyceride level and obesity in humans [30,48]. Hence, the hypermethylation event at the promoter region of SLC6A3, detected previously by our group [4], and its low expression in CRC, reported in the current study, could suggest an alteration in metabolism, such as lipogenic pathways, and probably a oxidative stress environment leading to malignancy transformation [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it was reported that Slc6a3 was hypermethylated in the promoter region in response to high-fat-sucrose diet and downregulated in the nervous system of prenatally stressed female rats and murine models of diet-induced obesity [46,47]. In addition, methylation aberrations at SLC6A3 gene were related to triglyceride level and obesity in humans [30,48]. Hence, the hypermethylation event at the promoter region of SLC6A3, detected previously by our group [4], and its low expression in CRC, reported in the current study, could suggest an alteration in metabolism, such as lipogenic pathways, and probably a oxidative stress environment leading to malignancy transformation [49].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has been reported that dopamine improves the efficacy of therapy in breast and colon cancer [29]. In a different context, hypermethylation was detected in dopamine pathway genes, including SLC6A3, as a consequence of a high fat and sugar diet suggesting a link between dopaminergic signalling and metabolic control [30].…”
Section: Introductionmentioning
confidence: 99%
“…; Ramos‐Lopez et al. ). According to a number of studies, the consumption of high‐fat and high‐carbohydrate diets, predisposing to obesity, causes persistent changes in the metabolism of dopamine, leading to disruption of the formation of a sense of food saturation (Lee et al.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, a number of other relevant genes were identified as being differentially methylated as a function of SES, including genes linked to psychiatric disorders (Zinc Finger [65,66], and metabolic function (Protein Phosphatase 2 Regulatory Subunit Bdelta) [67]. These findings are in line with previous literature showing that psychiatric disorders and immunosuppression is commonly observed in individual with low SES [68][69][70][71][72], as well as in individuals exposed to early-life SES adversity with significant down-regulation of glucocorticoid-related genes in blood [73] and placenta [14], which regulates the secretion of cortisol and transduces its anti-inflammatory actions in the immune system.…”
Section: Discussionmentioning
confidence: 99%